Eksplorasi Nilai-Nilai Budaya dalam Pembelajaran Karakter dan Moral Anak di TK Bukit Permai 2 - Febriani, A.Nurul; Amriani, Sri Rika; Musi, Muhammad Akil (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
The focus of this research is how local cultural values are integrated into character and moral education for children at TK Bukit Permai 2. This study employs a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The validity of the data is tested through triangulation of time, technique, and source, as well as collection, condensation, presentation, and conclusion drawing. The research results show that TK Bukit Permai 2 consistently integrates local cultural values into children's daily activities, such as the use of polite language ("iyye", "tabe"), the habit of greeting teachers, the practice of sharing food, and the reinforcement of empathy and mutual cooperation values through collaborative activities. Teachers also use culturally-based learning methods such as playing traditional games (dende/engklek), performing regional dances (Mappadendang), and storytelling folk tales rich in moral messages. These values are instilled through habituation, exemplary behavior, and socio-cultural approaches in accordance with the developmental theories of Vygotsky, Piaget, and constructivism. Parental support and synergy with the school environment strengthen the effectiveness of character education based on local culture. Children show improvement in character in aspects of empathy, discipline, responsibility, and respect.